A Study of the Legal Translation of Chinese Medical Terminology - Guo, Hongjun; Liu, Zixuan; Chen, Jing (International Journal of Public Health and Medical Research, 2025)
As a cultural treasure of China and an integral part of traditional Chinese cultural confidence, Traditional Chinese Medicinein (TCM) deserves both our appreciation and proper global dissemination. To better promote TCM on the international stage, we must first value it ourselves and ensure its accurate transmission. This study aims to explore ways to improve the accuracy of French translations of TCM-related content, with the ultimate goal of enhancing the effective dissemination of TCM culture across French-speaking regions worldwide.